Die einde van sending: fases in die sendingbedryf - J. J. Kritzinger (Acta Theologica)
In this article the author deals with the final phase of a mission project, that of handing over, or the phasing out of the work. Although the issue is addressed in general, and an overview is given of the theories that missiologists held since the 19th century, the questions are focused on the situation in the mission work of the Dutch Reformed Church of South Africa (NG Kerk). He thinks that much of the present relational problems between this church and its South African sister churches has to do with the fact that their “mission relations” were not really terminated. The article ends with some proposals to end the impasse.